(3QSGdI GdTghO GdYjfj aj GdhLhO GdPgfjs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Gddge jG MfGf jG efGf JbOSJ HPGJc Yf GdhLhO aj GdCPgGf hHYO agPg QSGdI GdTghO GdYjfj aj eHGMK GdhLhO GdPgfj deG JYGQcJ ajgG CPgGf GdYdeGA hJUGOeJ aj eTGgOgG BQGA GdaVdGA hGdQSGdI eQJHI Ydi ebOeI heSdcjf hNGJeIs
(3BNQgG (B:s
(3hefgG GdeGgjI GdMGUdI aj GdPgf Yde HGYJHGQ GdbjGe HGdfaS heYdhe HOhf gPG GdGYJHGQ hefgG GfgG LRFjI HGdGYJHGQ GdChd hcdjI Ch LRFjI HGdGYJHGQ GdKGfj Edi ZjQ Pdc ef GdahGFO GdJj dG oJMUi hdYeQ CfgG CLOi ef JaGQjb GdYUGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 257s
(3eYLe GdeDdajf (B1 / 308s
(3cTa GdXfhf (B2 / 1068s
(3TPQGJ GdPgH (B8 / 352s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds